Design and assessment of solar PV plant for girls hostel (GARGI) of MNIT University, Jaipur city: A case study. (November 2016) - Khatri, Rahul
Abstract: In this paper designing and assessment of a solar PV plant for meeting the energy demand of girl's hostel at MNIT University Jaipur city was analyzed. A solar PV plant was designed with its financial and environmental assessment considering recent market prices. All the aspects related to a solar PV plant were considered for financial feasibility of PV plant near this location. The different financial parameters which affect the financial feasibility of PV plant were considered i.e. discount rate, effective discount rate, rate of escalation of electricity cost, salvage value of the plant etc. The environmental aspect related with the energy generated with PV plant i.e. reduction in carbon emission and carbon credits earned was also considered. Result obtained with the assessment of the proposed plant with different discount rate and current rate of inflation shows that the max IRR 6.85% and NPV of $1, 430, 834 was obtained with a discount rate of 8% and an inflation rate of 7.23% when no land cost considered and if land cost was considered the maximum IRR was 1.96% and NPV of $630, 833. Minimum discounted payback of the plant will be 13.4 years if inflation was considered.